Christ and evolution : a study of the doctrine of redemption in the light of modern knowledge - Barton, George A. (George Aaron), 1859-1942 (University of Pennsylvania Press, 2017)
During these last years the writer has heard clergymen again and again confess that they did not know how to present the Gospel to the younger generation. The old bases of appeal are ineffective. The fear of Hell has gone; interest in immortality itself is absent from the minds of many; the old forms of appeal seem to many too individualistic and selfish to be inspiring. Many of the questions raised by modern knowledge are not met by the theologies that were formulated before the newer discoveries were made. The writer has found that young people heartily respond to the Gospel when garbed in the dress with which he has clothed it here, and that young clergymen go forth to their work with a new sense of mission and of the dignity of their calling when they understand that they are fellow workers with God in completing the creation of the human race.